2022
DOI: 10.2196/22113
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Nonuse, Discontinuation of Use, and Acceptance of Additional Functionalities of a COVID-19 Contact Tracing App: Cross-sectional Survey Study

Abstract: Background In several countries, contact tracing apps (CTAs) have been introduced to warn users if they have had high-risk contacts that could expose them to SARS-CoV-2 and could, therefore, develop COVID-19 or further transmit the virus. For CTAs to be effective, a sufficient critical mass of users is needed. Until now, adoption of these apps in several countries has been limited, resulting in questions on which factors prevent app uptake or stimulate discontinuation of app use. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Before the spread of the omicron variant of the SARS-CoV-2, epidemiological studies in the United Kingdom have found that CTAs are effective when adopted by the public [ 3 ]. A German study [ 10 ] found that a higher level of education led to improved adoption of pandemic apps. In Belgium, a survey found a large majority of nonusers This refusal of use was largely due to privacy concerns and ambivalence about the app’s utility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Before the spread of the omicron variant of the SARS-CoV-2, epidemiological studies in the United Kingdom have found that CTAs are effective when adopted by the public [ 3 ]. A German study [ 10 ] found that a higher level of education led to improved adoption of pandemic apps. In Belgium, a survey found a large majority of nonusers This refusal of use was largely due to privacy concerns and ambivalence about the app’s utility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three recent studies have assessed the characteristics and associations of users and nonusers of different mHealth apps, all using participants from the general population, but still lacking consensus. Walrave et al [ 25 ] identified no sociodemographic differences between users and nonusers of contact tracking alert apps, including the Belgian Corona alert app. A study of the general US population identified strong associations of age, gender, and education level with the use of fitness apps and calorie counters [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observed app uninstalling might be due to a lack of perceived bene ts from the app or due to experienced di culties in using the app. 8,42 App uninstalling among vaccinated participants, particularly, can also be explained by ongoing misconceptions during the alpha and delta variant waves that vaccination could prevent all SARS-CoV-2 infections, making app use seem unnecessary. 43 Nevertheless, our failure time analyses depicted a dichotomy of participants who did not use the SwissCovid app and did not get vaccinated (16% of pooled study population) versus participants who used the app and got vaccinated (40% of pooled study population) during the study period.…”
Section: Discussionmentioning
confidence: 99%